DI-078 Study of rituximab in off-label situations. (24th February 2014) - Raich Montiu, L; Frías López, MC; Cabré Serres, M; De Pedro Ambrosio, V; Gómez Valent, M; De Castro Julve, M; Borràs Trias, L; Gorgas Torner, MQ
Abstract : Background: Depletion of pre-mature and mature B lymphocytes due to rituximab leads to a range of possibilities for the treatment of inflammatory and autoimmune diseases. Purpose: To evaluate the efficacy and safety of rituximab in off-label treatment. Materials and methods: Observational, descriptive and retrospective study reviewing the medical records of patients using off- label rituximab treatment between January 2011 and December 2012. The primary endpoint was the efficacy of immunosuppressive treatment measured through the antinuclear antibodies (ANA), myeloperoxidase (MPO) and antineutrophil cytoplasmic antibodies (ANCA). Data were collected from medical records and pharmacy database. The number of cycles and doses administered was also described. The second endpoint was safety. The adverse reactions observed during the treatments were described. Results: In 2011, a total of 71 patients were treated with rituximab. Six of them (8%) were using rituximab off-label. In 2012, there were 28 patients using rituximab, seven included in the study. A total of 13 patients received rituximab as off-label treatment. The most common indication was vasculitis secondary to other pathologies in 7 patients (53%) followed by 4 systemic lupus erythematosus (SLE), an Onset Facial Syndrome Sensory Motor Neuron (FOSMN), one Idiopathic thrombocytopenic purpura (ITP) and an extracapillary glomerulonephritis. The remaining indications were haematological, dermatological, renal and ophthalmological. The mean number of cycles was 4 per patient. The most common dose was 375 mg/m 2 . Most of the patients showed a partial response to the treatment and only one patient had to discontinue treatment because of recurrence at 6 months. 3 adverse reactions to the infusion were observed. One respiratory condition finally focused on pneumonia (after Streptococcus pneumoniae had been isolated), and 2 had symptoms of anaphylaxis. Both resolved upon further administrations. Conclusions: Though efficacy was not very apparent, rituximab has been used as a treatment for vasculitis and other inflammatory and autoimmune disease in recent years. In most cases rituximab was well tolerated, and there were no severe infusion reactions. No conflict of interest.